The Influence Of Trust And Service Quality On Public Satisfaction (Case Study At The Ratu Agung Sub-District Office, Bengkulu City) - Sendi Nopriansyah; Ida Ayu Made E.G; Kamelia Astuty (Universitas Dehasen Bengkulu, 2026)
Public satisfaction is an important indicator in assessing service performance in both government and private institutions that provide services. Satisfaction can be measured and observed from various aspects, one of which is consumer trust in the services received after engaging with a particular institution or service provider. The purpose of this study is to determine the extent to which trust and service quality influence public satisfaction at Ratu Agung Sub-District Office, Bengkulu City. This research is categorized as a quantitative study with a causal associative approach. The data collection method used a questionnaire with a Likert scale, and the sample consisted of 50 respondents who received services at Ratu Agung Sub-District Office at the time of the study. The results of the study indicate that the multiple linear regression equation obtained is:Y = 10.696 + 0.286 (X1) + 0.457 (X2) + 3.312, which means that there is a positive (direct) correlation between trust (X1) and service quality (X2) on public satisfaction (Y) at Ratu Agung Sub-District Office, Bengkulu City. The hypothesis testing for trust (X1) shows that t-count = 2.018>t-table = 2.011 and significance value = 0.049 < 0.05. Thus, Ha is accepted and Ho is rejected, indicating that trust has a significant effect on public satisfaction. Meanwhile, the test for service quality (X2) shows that t-count = 3.390>t-table = 2.011 and significance value = 0.001<0.05. Therefore, Ha is accepted and Ho is rejected, indicating that service quality also has a significant effect on public satisfaction. Furthermore, F-test result shows that F-count = 34.134>3.195, indicating that the hypothesis is accepted. This means that there is a simultaneous effect of trust (X1) and service quality (X2) on public satisfaction (Y) at Ratu Agung Sub-District Office, Bengkulu City.